International Law of the Sea and Marine Affairs: A Bibliography. Supplement to the 1980 Edition - Papadakis, N.; Glassner, Martin Ira (M. Nijhoff ; Distributors for the U.S. and Canada, Kluwer Boston, 1984)
Keywords: Bibliography; Maritime law; dept.egm; faculty_collection

John Paul Goode, 1862-1932. - Martin, G.J. (Geographers: biobibliographical studies, vol. 8, 1984)
In 1901 Goode obtained his doctorate - only the second in the USA to break away from the geology/physiography tradition. As his career developed he increasingly specialized in cartography, developed coloured wall maps for Rand McNally, and an interrupted homolosine projection. His name has survived on a school atlas for over 60 years. There is a chronological bibliography and a summary of his life.-K.Clayton
Keywords: dept.egm; ⛔ No DOI found

Selected Essays 1963-1975 - Sauer,carl,o. - Callahen,b - Martin, GJ (Professional Geographer, 1984)
tex.unique-id: ISI:A1984SR99000029
Keywords: dept.egm; ⛔ No DOI found

Change and development in the middle-east - clarke,ji, bowenjones,h - Glassner, MI (Journal of Developing Areas, 1984)
tex.unique-id: ISI:A1984ABS2000013
Keywords: dept.egm; ⛔ No DOI found

Contest for the south china sea - samuels,ms - Glassner, MI (Political Geography Quarterly, 1984)
0 citations (Crossref) [2023-10-31] tex.unique-id: ISI:A1984TB24000008
Keywords: dept.egm

Land-locked states and the unclos regime - sinjela,am - Glassner, MI (American Journal of International Law, 1984)
0 citations (Crossref) [2023-10-31] tex.unique-id: ISI:A1984TD35000028
Keywords: dept.egm

Mackinder - geography as an aid to statecraft - parker,wh - Glassner, MI (Professional Geographer, 1984)
tex.unique-id: ISI:A1984TE16200056
Keywords: dept.egm; ⛔ No DOI found

The Red-Sea and the Gulf of Aden - Lapidotheschelbacher,r - Glassner, MI (Political Geography Quarterly, 1984)
0 citations (Crossref) [2023-10-31] tex.unique-id: ISI:A1984TQ87300015
Keywords: dept.egm